Birds of a Feather: Some Fundamentals on the Archives-Ecology Paradigm - Moore, Erik A. (Archivaria, 2007)
This article reviews the concepts of preservation, conservation, and ecology in order to establish archival theory and practice, and environmental philosophy and protection as intellectually related domains, not merely analogous subjects. Moving beyond the organic metaphor peppered throughout the professional literature, it challenges archivists to look more widely at the parallel ideas and applications in archives and ecology that can influence and inform their decisionmaking process, and encourages archivists to move further away from the positivism that has directed much of their activities toward a more pluralistic paradigm evident in the biological and physical sciences. The outcome is a fundamental understanding of the theoretical intersection of archives and ecology coupled with models that can guide practical applications in appraisal and access for archives. RÉSUMÉ Cet article passe en revue les concepts de préservation, de conservation et d’écologie, en vue d’établir le lien entre la théorie et la pratique archivistiques, ainsi que la philosophie et la protection environnementales, comme des domaines qui sont intellectuellement liés et non seulement analogues. En dépassant la métaphore de l’organique qui est omniprésente dans la littérature professionnelle, l’auteur invite les archivistes à examiner les idées et les applications parallèles tant au niveau des archives que de l’écologie qui peuvent agir sur le processus de prise de décision. Il encourage de plus les archivistes à s’éloigner du positivisme qui a souvent guidé leurs activités, pour se diriger plutôt vers un paradigme plus pluraliste tel qu’il se présente dans les sciences biologiques et physiques. Le résultat est une connaissance fondamentale de l’intersection théorique entre archives et écologie, en lien avec des modèles qui peuvent mener vers des applications pratiques dans l’évaluation et l’accès des archives.